Timothy A. Johnson, John Adams’s Nixon in China: Musical Analysis, Historical and Political Perspectives (2011) - ap Siôn, Pwyll (Journal of the Society for Musicology in Ireland, 2013)
Review of Timothy A. Johnson, John Adams’s Nixon in China: Musical Analysis, Historical and Political Perspectives (Farnham: Ashgate Press, 2011). ISBN 978-1-4094-2682-0.